Raya in Türkiye: My First Aidilfitri Abroad as A UMPSA Student in Istanbul A Snowy Start to a New Chapter - Siti Maizurah, Zulkafli (UMPSA, 2025)
My name is Siti Maizurah Zulkafli, and this is my Raya story. This year, I celebrated my very first Hari Raya Aidilfitri away from home, and it was an experience I will never forget. I arrived in Istanbul last February, greeted by heavy snow. That was how my journey here began.